'Colloquialization' in fiction: A corpus-driven analysis of present-tense fiction. (August 2019) - Ikeo, Reiko
Over the past decade, more and more writers have used the present tense as the primary tense for their fictional narratives. This article shows that contemporary present-tense fiction has more lexical and syntactic characteristics which are similar to spoken discourse than past-tense fiction by comparing lexis and structures in two corpora: a corpus consisting of present-tense narratives and a corpus of past-tense narratives. It also discusses how the use of the present tense affects the management of viewpoint in narrative by relating its lexical, structural characteristics to the presentation of characters' speech and thoughts.